Phylogenetic Analysis of Dengue Virus in Bangkalan, Madura Island, East Java Province, Indonesia - Teguh Hari Sucipto; Tomohiro Kotaki; Kris Cahyo Mulyatno; Siti Churrotin; Amaliah Labiqah; Soegeng Soegijanto; Masanori Kameoka (Journal of Tropical Medicine)
Dengue virus (DENV) infection is a major health issue in tropical and subtropical areas. Indonesia is one of the biggest dengue endemic countries in the world. In the present study, the phylogenetic analysis of DENV in Bangkalan, Madura Island, Indonesia, was performed in order to obtain a clearer understanding of its dynamics in this country. A total of 359 blood samples from dengue-suspected patients were collected between 2012 and 2014. Serotyping was conducted using a multiplex Reverse Transcriptase-Polymerase Chain Reaction and a phylogenetic analysis of E gene sequences was performed using the Bayesian Markov chain Monte Carlo (MCMC) method. 17 out of 359 blood samples (4.7%) were positive for the isolation of DENV. Serotyping and the phylogenetic analysis revealed the predominance of DENV-1 genotype I (9/17, 52.9%), followed by DENV-2 Cosmopolitan type (7/17, 41.2%) and DENV-3 genotype I (1/17, 5.9%). DENV-4 was not isolated. The Madura Island isolates showed high nucleotide similarity to other Indonesian isolates, indicating frequent virus circulation in Indonesia. The results of the present study highlight the importance of continuous viral surveillance in dengue endemic areas in order to obtain a clearer understanding of the dynamics of DENV in Indonesia.